NILAI FILOSOFI JAWA DALAM SERAT CENTHINI - Sutrisna Sutrisna Wibawa (LITERA, 2013)
This study aims to reveal and formulate Javanese philosophical values and philosophical foundations in Serat Centhini. It was a qualitative descriptive study. The data source was the Serat Centhini text. The research steps included data collection, data reduction, data display, and conclusion drawing. The data were analyzed using the hermeneutic and heuristic techniques. The findings are as follows. First, Javanese philosophical values in Serat Centhini are reflected in Javanese cultural contents and philosophy reflecting the Javanese society when Serat Centhini was written. The Javanese philosophy in Serat Centhiniis reflected by the life perfection value (ngudi kasampurnan) and the philosophy of origin and destination (sangkan paraning dumadi). Second, the philosophy in Serat Centhini is reflected in the ontological, epistemological, and axiological foundations.